THE EFFECT OF LECTURING WITH BOOKLET MEDIA TOWARDS ON KNOWLEDGE OF POSYANDU CADRES - Juin Hadisuyitno (STIKES Karya Husada Kediri, 2014)
ABSTRACT The use of methods with lecture and discussion and answer on posyandu cadres have not been able to increase on knowledge in prevention efforts IDD. The use of media education can facilitate the delivery of information. The combination is expected to use extension methods presented information readily accepted and understood. The effect of extension methods with the media booklet on knowledge, attitudes and skills posyandu cadres. The study is quasi experiment pre post non randomized control group design. Sample is consisted of 66 posyandu cadres in the health centers Junrejo region are divided 2 groups, the intervention group consisted of 33 posyandu cadres given of lecturing the method lecture, discussion and demonstration as well as given a booklet and 33 posyandu cadres control group obtain lecture without given a booklet. Measurements score on knowledge performed 3 times before, after and one month after intervention. Statistical test using the Wilcoxon Signed Rank Test and Mann Whitney. There were significant differences in score mean knowledge (p = 0.0001between before and after one month intervention. Both groups showed significant difference score mean knowledge (p = 0.0001) and skills (p = 0.028), but not on the score mean attitude (p = 0.368) at the end of the study. Extension methods by providing booklet media can improve knowledge, attitudes and skills posyandu cadres in prevention efforts IDD. Keywords: knowledge, posyandu cadres, booklet.